Wasathiyah sebagai Jembatan Timur–Barat: Kerangka Maqasid untuk Dialog Peradaban - Asdianur Hadi; Endi Suhendi (Lembaga Pengembangan Kinerja Dosen, 2026)
This article proposes wasathiyah—a balanced Islamic ethic grounded in the maqasid al-shari‘ah—as a practical framework for East–West civilizational dialogue. It critiques “clash of civilizations” narratives for reducing cross-cultural relations to identity antagonism, while historical experience points to more complex patterns of exchange, negotiation, and mutual correction. By using maqasid as a normative compass, dialogue is oriented toward publicly verifiable aims: safeguarding human dignity, advancing justice, protecting reason and knowledge, strengthening social cohesion, and promoting sustainable governance. The discussion draws on Nahdlatul Ulama’s tradition of Aswaja An-Nahdliyah and contemporary discourse on fiqh al-hadlarah (civilizational jurisprudence) to formulate an indicator matrix across key domains—education, law and human rights, economy, media, and emerging technologies (including AI)—along with a 3–5 year implementation roadmap and risk-mitigation strategies. The article concludes by highlighting implications for Islamic education, particularly academic integrity, digital-ethical literacy, and interdisciplinary projects oriented to the public good (maslahah).